2014
DOI: 10.1021/cg500190h
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscaled M-MOF-74 Materials Prepared at Room Temperature

Abstract: This paper describes the preparation and characterization of nano-scaled M-MOF-74/CPO-27-M (M = Mg, Mn, Co, Ni and Zn) materials at room temperature. Some of the soformed crystals are the smallest ones of any MOF material (and, to the best of our knowledge, of any microporous material) ever reported. They are in the limit of being able to diffract, particularly these forming the Co-and Ni-MOF-74 samples. Consequently, unequivocal identification as crystalline MOF-74 phase was deduced by combining other charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
142
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(167 citation statements)
references
References 49 publications
16
142
1
8
Order By: Relevance
“…In addition, the broad peaks observed in XRD pattern for the synthesis with DMF only (F1) suggests that nano-crystals are produced. The size of the crystals from formulation F1 (DMF-only) formed after 6 h at 125°C was calculated as 8.0 nm, showing good agreement with previously report 38 . When the volume of water and ethanol was increased in the synthesis solutions (from F1 to F4) the intensity of the characteristic XRD peaks (6.7°and 11.7°) for Mg-MOF-74 increased and sharper peaks were obtained.…”
Section: Single Gas Permeation Measurementssupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the broad peaks observed in XRD pattern for the synthesis with DMF only (F1) suggests that nano-crystals are produced. The size of the crystals from formulation F1 (DMF-only) formed after 6 h at 125°C was calculated as 8.0 nm, showing good agreement with previously report 38 . When the volume of water and ethanol was increased in the synthesis solutions (from F1 to F4) the intensity of the characteristic XRD peaks (6.7°and 11.7°) for Mg-MOF-74 increased and sharper peaks were obtained.…”
Section: Single Gas Permeation Measurementssupporting
confidence: 90%
“…Further images of the alumina surface after synthesis using formulation F1 are shown in the supplementary information ( Figure S5). Using only DMF (F1), the crystals formed have a diameter of around 8 nm as reported by Díaz-García et al 38 (confirmed with the Scherrer equation) and are prone to agglomeration, as can also be seen in Figure S1. The nano-sized particles may not readily attach to the surface of the alumina substrate, most likely because the crystals are much smaller than alumina substrate pores (200 nm).…”
Section: Controlling Mg-mof-74 Film Thicknesssupporting
confidence: 82%
See 1 more Smart Citation
“…Note that characterization of MOFs by TEM/STEM is notoriously challenging because of the high susceptibility of the organic linkers to electron beam induced degradation 19–21 . Our high-resolution microscopy data are the first such available on Co-MOF-74 nanocrystals to date 19, 20, 22 .
Figure 2( a ) BF TEM image of agglomerated Co-MOF-74 nanocrystals. ( b ) SAED pattern of such nanocrystals in which the extracted radial intensity profile in the overlay confirms their Co-MOF-74 structure 18 .
…”
Section: Resultsmentioning
confidence: 99%
“…Following a similar procedure, M-MOF-74 nanocrystals with a narrow size distribution (M = Mg, Mn, Co, Ni, Zn) were immediately isolated adding dropwise a DMF solution of 2,5-dihydroxyterphthalic acid (DHTP) over a DMF solution containing the corresponding divalent metal acetate tetrahydrate [197]. On the opposite, by using slow diffusion and long reaction times (more than one week), large crystals of MOF-2, MOF-3 and MOF-5 [198][199][200], have been synthesized from metal salt Zn(NO 3 ) 2 and 1,4-benzenedicarboxylic acid (H 2 BDC).…”
Section: Diffusion Controlled Synthesismentioning
confidence: 99%